Serial mom [videorecording (DVD)] - Waters, John, 1946-; Turner, Kathleen, 1954-; Waterston, Sam; Lake, Ricki (Universal Studios Home Entertainment, 2008)
Beverly Sutphin is a seemingly perfect homemaker who will stop at nothing to rid the neighborhood of anyone failing to live up to her moral code.